Spiritual Identities, Teacher Identities, and the Teaching of Writing - Kilian McCurrie (Journal of the Assembly for Expanded Perspectives on Learning, 2003)
Through a case study, this article examines the ways teacher identity and spiritual identity intersect in the teaching of writing. By showing that a teacher's pedagogy is prodoundly informed by a basic spiritual disposition, the author offers a view of teaching that is often neglected in studies of teacher identity.